Acute intestinal failure: International multicenter point-of-prevalence study. Issue 1 (January 2020) - ,; Mihnovits, Vladislav; Britenkova, Antonina; Lind, Kadri; Pertsev, Ivan; Lansche, Gregor; Sasdelli, Anna Simona; Bodnar, Zsolt; Pracca, Francisco; Bioni, Italo; Kekstas, Gintautas; Venlavicute, Karolina; et al.
Summary: Background & aims: Intestinal failure (IF) is defined from a requirement or intravenous supplementation due to failing capacity to absorb nutrients and fluids. Acute IF is an acute, potentially reversible form of IF. We aimed to identify the prevalence, underlying causes and outcomes of acute IF. Methods: This point-of-prevalence study included all adult patients hospitalized in acute care hospitals and receiving parenteral nutrition (PN) on a study day. The reason for PN and the mechanism of IF (if present) were documented by local investigators and reviewed by an expert panel. Results: Twenty-three hospitals (19 university, 4 regional) with a total capacity of 16, 356 acute care beds and 1237 intensive care unit (ICU) beds participated in this study. On the study day, 338 patients received PN (21 patients/1000 acute care beds) and 206 (13/1000) were categorized as acute IF. The categorization of reason for PN was revised in 64 cases (18.9% of total) in consensus between the expert panel and investigators. Hospital mortality of all study patients was 21.5%; the median hospital stay was 36 days. Patients with acute IF had a hospital mortality of 20.5% and median hospital stay of 38 days (P > 0.05 for both outcomes). Disordered gut motility (e.g. ileus) was the most common mechanism of acute IF, and 71.5% of patients with acute IF had undergone abdominal surgery. Duration of PN of ≥42 days was identified as being the best cut-off predicting hospital mortality within 90 days. PN ≥ 42 days, age, sepsis and ICU admission were independently associated with 90-day hospital mortality. Conclusions: Around 2% of adult patients in acute care hospitals received PN, 60% of them due to acute IF. High 90-day hospital mortality and long hospital stay were observed in patients receiving PN, whereas presence of acute IF did not additionally influence these outcomes. Duration of PN was associated with increased 90-day hospital mortality.